Regional Economic Outlook, September 2006, Middle East and Central Asia. (Regional Economic Outlook, 2006)
This paper presents the economic outlook for the Middle East and Central Asia for 2006-07. Economic performance in the Middle East and Central Asia region remains strong, despite security problems in some countries and recent asset price reversals. Growth in the region continues to outpace global growth and should average 6-7 percent in 2006 and 2007-similar to the rates of the past three years. Strong external inflows resulting from high oil and non-oil commodity prices, foreign investments, and remittances are fueling credit growth, and inflation continues to edge up.